Ayurvedic Approach to Managing Hyperuricemia: A Case Study - Lata, Suman; Kumar Tiwari, Satyendra (Journal of Neonatal Surgery, 2025)
Hyperuricemia is a metabolic disorder that occurs due to elevated serum uric acid levels, a byproduct of purine metabolism. This condition may affect individuals across different age groups and is commonly associated with gout, a form of inflammatory arthritis characterized by intense joint pain. In Ayurvedic literature, such presentations align closely with Vatarakta, a condition arising from the vitiation of Vata and Rakta Doshas.This case involves a 66-year-old male who presented with persistent bilateral knee discomfort, along with severe pain, swelling, and redness localized to the right great toe. The symptoms were present for approximately three years and significantly impacted his mobility and quality of life.He was administered a classical Ayurvedic regimen from April 28, 2024, to May 23, 2024, consisting of Kaishora Guggulu, Samshamani Vati, Kokilakshadi Kwatha, and Sarivadyasava. Over the course of the treatment, notable symptomatic relief was observed. Inflammation, pain, and tenderness gradually subsided, and his serum uric acid levels reduced from 8.50 mg/dl to 5.83 mg/dl.This case highlights the potential of Ayurvedic formulations in effectively managing gouty arthritis, offering both symptomatic relief and biochemical improvement